The workings of treasuries in Greek sanctuaries - Barringer, Judith M. (Opuscula. Annual of the Swedish Institutes at Athens and Rome, 2025)
Thesauroi are common in Greek sanctuaries, as we know from epigraphical, literary and physical evidence, although written sources, especially inscriptions, are often ambiguous as to whether they refer to money boxes or buildings since the same term can be used for either. Scholars have long studied the latter, particularly the architecture and sculpture of those at Olympia and in the Apollo sanctuary at Delphi. Far less attention has been given to the administration, placement, accessibility and the motivations for constructing these buildings. This paper gathers and discusses the evidence concerning these issues to better understand these common structures and their use and function within sanctuaries.